Magnetic Resonance Imaging of the Effortful Swallow. (November 2014) - Fritz, Mark; Cerrati, Eric; Fang, Yixin; Verma, Avanti; Achlatis, Stratos; Lazarus, Cathy; Branski, Ryan C.; Amin, Milan
Objective: The effortful swallow was designed to improve posterior mobility of the tongue base and increase intraoral pressures. We characterized the effects of this maneuver via dynamic magnetic resonance imaging (dMRI) in healthy patients. Methods: A 3-T scanner was used to obtain dMRI images of patients swallowing pudding using normal as well as effortful swallows. Ninety sequential images were acquired at the level of the oropharynx in the axial plane for each swallow; 3 series were obtained for each swallow type for each patient. Images were acquired every 113 ms during swallowing. The images were analyzed with respect to oropharyngeal closure duration, anteroposterior and transverse distance between the oropharyngeal walls, and oropharyngeal area before and after closure. Results: Preswallow reduced pharyngeal area was observed ( P = .02; mean = 212.61 mm 2 for effortful, mean = 261.92 mm 2 for normal) as well as prolonged pharyngeal closure during the swallow ( P < .0001; mean = 742.18 ms for effortful, mean = 437.31 ms for normal). No other differences were noted between swallow types. Interrater and intrarater reliability of all measurements was excellent. Conclusion: This preliminary investigation is the first to evaluate the effects of effortful swallows via dMRI. In our cohort, consistent physiologic changes were elicited, consistent with clinical dogma regarding this maneuver.